Variability management with feature models - Schröder-Preikschat, Wolfgang; et al. (Science of Computer Programming, 2004)
Variability management in software systems requires adequate tool support to cope with the ever increasing complexity of software systems. The paper presents a tool chain which can be used for variability management within almost all software development processes. The tools presented use extended feature models as the main model for describing variability and commonality, and provide user changeable customization of the software artifacts to be managed. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.tech.IMMD.IMMD4.variab
Keywords: Feature modeling; Tool support; Variant management